The Trauma Theme of "You Fly to Your Mountain Like a Bird" from the Perspective of Trauma Theory - Wu, Xixi (Journal of Theory and Practice of Contemporary Education, 2023)
"You Fly Like a Bird to Your Foot" records the thoughtless yet inspiring life experiences of American white woman Tara Westford through a personal biography. From the perspective of trauma theory, this article explores the trauma theme of the book: interpreting the sources of Tara's individual trauma, namely the psychological trauma brought to Tara by her native family; Analyze Tara's journey of self discovery, that is, the path through which Tara repairs wounds and seeks her true self; And explore narrative strategies for reproducing traumatic memories, such as autobiographical novel forms and location depictions. Education bridged the psychological trauma brought to Tara by her native family and gave her the courage and strength to fly to her own forest.